Neoadjuvant chemoradiotherapy plus sintilimab in pMMR/MSS rectal cancer patients with PD-L1 TPS ≥ 1% or CPS ≥ 1: an open-label, prospective, phase II study - Zhenlin Hou; Leen Liao; Weiwei Xiao; Qiaoqi Sui; Kai Han; Binyi Xiao; Yuan Li; Weijian Mei; Jiehai Yu; Zhigang Hong; Qichen Chen; Ruyue Song; et al. (npj Precision Oncology)
Abstract This phase II clinical trial aimed to evaluate the efficacy and safety of neoadjuvant long-course chemoradiotherapy combined with sintilimab in mismatch repair-proficient (pMMR)/microsatellite-stable (MSS) locally advanced rectal cancer (LARC) patients with a PD-L1 tumor proportion score (TPS) ≥1% or combined positive score (CPS) ≥1. The primary endpoint was pathological complete response (pCR), and safety was assessed. This trial was registered on ClinicalTrials.gov (identifying number: NCT04833387) with the registration date of April 4, 2021. Although the target pCR rate was not fully achieved, a notable improvement was observed, with 7/20 (35.0%) patients achieving pCR in the intention-to-treat analysis. A trend toward higher pCR rates was observed in patients with PD-L1 CPS ≥ 5 than in those with CPS < 5 (50.0% vs. 27.3%, P = 0.311). Treatment-related adverse events occurred in 12 patients (60.0%), with no grade 4 events. Biomarker analysis revealed that higher CD3 (P < 0.001) and CD8 (P = 0.018) expression, along with lower TIM-3 (P = 0.017) expression in the stroma, was associated with higher pCR rates.